Pemberdayaan Perempuan dalam Pendidikan Pesantren - Dwi Ratnasari (Institut Ilmu Keislaman Annuqayah, 2016)
Empowerment means building awareness about women’s ability to independently determine their life as a human being, without dependence, distress and discrimination. since it’s inception, Islam has affirmed transformation of women without equate with men. Education is an important instrument of the transformation that starts from knowledge to build awareness. The Pesantren (Islamic Boarding school) has a role in this process. Because it’s teachings are based on the teachings of religion to form awareness and attitude based on the religion. However, there are some problems in the curriculum, materials and education methods. Because the curriculum and materials of pesantren based on the explanation in yellow books which are the interpretation of the Muslim scholars on The Holy Koran and Al-Hadith. While, The contents of the yellow book are indicated gender discrimination by some researchers, like the 'Uqu>d al-Lujjain which is become foundation of almost all traditional pesantren. In this case, pesantren need to interact with modern knowledge in gender issues in order to create gender sensitivity. In addition, they need an introduction to the critical learning and improvment the professionalism of the teachers. With that, the education process of pesantren will be more empowered, progressive and in line with the principles of Islam.